THE EFFECT OF LIVE WEIGHT OF COWS ON THEIR MILK PRODUCTIVITY - Kharzhau, A.; Shamshidin, A. S.; Batyrgaliyev, Y. A.; Zholdasbekov, A. K. (Ғылым және білім=Наука и образование=Science and education № 3-2 (68), 2022)
Dairy productivity of cows depends on many factors: breed, live weight, feeding, age, well- being of cattle, environmental factors, etc. The paper presents data on dairy productivity of cows of breeding farms of Aktobe region «Esbol» and «Anisan». The average dairy productivity of cows for 305 days was 3898 kg in the Esbol farm, 3575 kg in the Anisan farm. Indicators of the mass fraction of fat and protein in milk were higher in Simmental cows compared to black-and-white cows. The influence of live weight of cows on the value of their milk productivity has been established. The highest milk yields and the amount of milk fat were characterized by animals that had a live weight above 500 kg. Cows with a low live weight of up to 450 kg had the lowest milk yield among the studied groups of animals.Молочная продуктивность коров зависит от многих факторов: породы, живой массы, кормления, возраста, самочувствия скота, факторов внешней среды и др. В работе представлены данные по молочной продуктивности коров племенных хозяйств Актюбинской области «Есбол» и «Анисан». Средняя молочная продуктивность коров за 305 дней составила в КХ «Есбол» 3898 кг, в КХ «Анисан» – 3575 кг. Показатели массовой доли жира и белка в молоке оказались выше у симментальских коров по сравнению с черно-пестрыми коровами. Установлено влияние живой массы коров на величину их молочной продуктивности. Наивысшими удоями и количеством молочного жира характеризовались животные, которые имели живую массу выше 500 кг. У коров с низкой живой массой – до 450 кг были самые минимальные показатели по удою среди исследуемых групп животных.
Keywords: отечественное издание; научный журнал; журнал коксон; периодическое издание; ринц; Simmental breed; black-white breed; productivity indicators; milk yield indicators; молочная продуктивность коров; молочный жир; удой молока